The Influence of Social Media Advertisements And E-WOM Towards Consumer Purchase Intentions on Skintific - Salsabila, Dita Fathima; Indrawati , Indrawati (ADPEBI, 2024)
The rapid rise in social media users has introduced social media advertising as a crucial tool for businesses. Advertisers face the significant challenge of low consumer acceptability of commercials, making it vital to identify key elements that influence consumer perceptions. In Indonesia, social media advertising ranks third with a 72% influence, particularly for skincare products, which are expected to grow annually by 4.10%. Local cosmetic companies face intense competition, necessitating innovative marketing strategies that leverage social media advertisements and the e-WOM phenomenon to increase interest, as seen with Skintific's popularity on social media. This research aims to study the influence of social media advertisement and e-WOM on the purchase intention of Skintific products. Using a quantitative method, the study analyzes internal factors of social media advertisements, including creative characteristics, celebrity endorsement, attention-grabbing details, and emotional appeal, with e-WOM as an additional variable. Data was collected from 300 respondents via a Google Form questionnaire targeting Indonesian social media users familiar with Skintific. PLS-SEM with SmartPLS was used to predict purchase intention. The results show that creative characteristics, celebrity endorsements, attention-grabbing details, emotional appeal, and e-WOM of Skintific products on social media advertisements significantly and positively influence purchase intention. Future research should explore additional features and different objects to enhance the effectiveness of social media advertisements and e-WOM in driving purchase intentions.